Peningkatan Kesehatan Gigi dan Mulut dengan Budaya 4 Tepat 5 Sempurna di Jorong Gurun Aur - Muhammad Faisal; Eka Sukanti; Dewi Susanti; Dewi Rosmalia (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
This community service program aimed to improve oral and dental health among the residents of Jorong Gurun Aur, Kenagarian Kubang Putih, Kecamatan Banuhampu, Kabupaten Agam. The main issue addressed was the lack of knowledge regarding proper toothbrushing techniques, which contributed to high cases of dental caries and other oral health problems. The program involved 13 elderly participants, 12 mothers with toddlers, and 52 TPA students. Activities included health education, demonstrations of toothbrushing techniques using the "4 Right 5 Perfect" method, and dental hygiene evaluations (Hygiene Index). Pre- and post-tests were conducted to evaluate knowledge improvement, while dental hygiene was assessed before and after the activities. The results indicated significant improvements. Among TPA students, the percentage of good dental hygiene increased from 22% to 88%, and good knowledge rose from 27% to 96%. For mothers with toddlers, good dental hygiene remained at 67%, but their good knowledge increased from 33% to 92%. The program successfully encouraged new behaviors, such as brushing teeth twice daily using proper techniques. In conclusion, this program effectively improved dental hygiene and oral health through education and practical demonstrations.